Spillover Effect of US Monetary Policy to ASEAN Stock Market - Aniek Hindrayani; Fadikia K Putri; Inda F Puspitasari (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2019)
Abstract: This study analyzes the spillover effects of the US monetary policy on the ASEAN stock market with Markov switching model and investigates differences in empirical results of each country from ASEAN member. The results of this study have important implications for asset price allocation, specifically in the case of a transition between US and other small countries. The results showed that the ASEAN stock market is more affected by the US interest rates during bull-market than bear-markets. This can be seen from the increasing of stock market volatility during expansion comparing with recession period. Therefore, the stock markets of ASEAN countries will not be easily affected by the dollar rate during financial crisis or the recession period. Keywords: stock market, monetary policy, spillover effect, Markov-switching modelEfek Spillover pada Perubahan Kebijakan Moneter Amerika Terhadap Stock Market di ASEANAbstrak: Penelitian ini menganalisis efek spillover akibat adanya perubahan kebijakan moneter Amerika terhadap stock market di ASEAN dengan model Markov switching dan menginvestigasi terkait ada atau tidaknya perbedaan pada hasil empiris di setiap negara anggota ASEAN. Hasil penelitian ini memberikan implikasi penting bagi mekanisme transisi harga aset, khususnya dari Amerika terhadap negara dengan skala perekonomian kecil. Hasil penelitian menunjukkan bahwa stock market ASEAN lebih mudah terpengaruh oleh tingkat suku bunga Amerika pada saat kondisi bull-market dibandingkan saat bear-market. Hal ini dapat dilihat dari tingginya volatilitas stock market pada saat ekspansi dibandingkan saat periode resesi, sehingga stock market negara-negara ASEAN tidak akan mudah terpengaruh oleh dollar pada saat perekonomian mengalami krisis atau saat periode resesi. Kata kunci: stock market, kebijakan moneter, spillover effect, model Markov-switching